Enhanced Photocatalytic Performances of SnS2/TiO2 Composites via a Charge Separation Following Z-Scheme at the SnS2/TiO2{101} Facets - Carl, Nkenku; Fiaz, Muhammad; Oh, Hyun Seok; Kim, Yu Kwon (Catalysts, 2024)
The formation of heterojunctions for efficient charge separation has been practiced for the preparation of efficient semiconductor-based photocatalysts for applications such as hydrogen production and environmental remediation. In this study, we synthesized a composite structure with a heterojunction between SnS2 and TiO2 through a microwave-assisted hydrothermal process, in which SnS2 nanoparticles grew on nanocrystalline TiO2 nanosheets preferentially at the exposed {101} facets. Appropriate exposure of the {001} and {101} facets of the TiO2 nanosheet in the composite with a preferential growth of SnS2 nanoparticles at the {101} facets was the origin of the charge separation following a direct Z-scheme mechanism to result in enhanced photocatalytic performances in photodegradation of organic dyes such as methylene blue (MB) and rhodamine B (RhB) compared to that of SnS2 and TiO2 alone. A plot of photodegradation rates vs. SnS2 ratios in the composites gave an overall volcano-shaped curve with a maximum at the SnS2 ratio of about 33% at which small SnS2 nanoparticles were populated at the {101} facets of the TiO2 nanosheets with a high surface area (118.2 m2g−1). Our results suggest the microwave-assisted hydrothermal process can be a good synthetic approach for composite-based photocatalysts with a preferential heterojunction structure.
Keywords: 2D metal dichalcogenides; heterojunctions; photodegradation; SnS2 nanoparticles; TiO2 nanosheets